2010
DOI: 10.1292/jvms.09-0476
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Autoantibodies against Survivin in Sera from Cancer Dogs

Abstract: ABSTRACT. Survivin overexpression has been reported in relation to tumor malignancy, suggesting that it is an unfavorable prognostic marker, and antibody responses to this protein have been confirmed in human cancer patients. In this study, we investigated antibody responses to survivin in canine cancer cases, and examined the prevalence of such responses by enzyme-linked immunosorbent assay (ELISA) using recombinant canine survivin protein as the antigen. The cut-off value for positivity in the anti-survivin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…16 The present data add further evidence of survivin involvement in mammary gland carcinogenesis and to the theory that inhibition of the molecule may be a viable therapeutic option. Furthermore, the immunogenic proprieties of survivin, demonstrated by the presence of autoantibodies and specific T cells against survivin in the blood of patients with breast cancer, 2 as well as of autoantibodies in dogs with mammary adenocarcinoma, 27 allow us to consider survivin a valid therapeutic target for anticancer immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…16 The present data add further evidence of survivin involvement in mammary gland carcinogenesis and to the theory that inhibition of the molecule may be a viable therapeutic option. Furthermore, the immunogenic proprieties of survivin, demonstrated by the presence of autoantibodies and specific T cells against survivin in the blood of patients with breast cancer, 2 as well as of autoantibodies in dogs with mammary adenocarcinoma, 27 allow us to consider survivin a valid therapeutic target for anticancer immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In one of our previous studies, autoantibodies to survivin were detected in 27.1% of cancer dogs, and this represented a significant difference from control populations consisting of normal and non-cancer disease dogs [13]. The highest positivity rates (>50%) among cancer cases were seen in dogs with mammary tumor, squamous cell carcinoma and melanoma, suggesting that canine survivin is expressed in many canine melanoma tissues [13]. The present study provides further evidence of the importance of survivin in canine melanoma for inducing apoptosis, and reinforces the notion of survivin as a putative therapeutic target in tumors.…”
mentioning
confidence: 69%
“…We also detected survivin expression in canine mammary tumors and melanoma tissue by immunohistochemical analysis (data not shown). In one of our previous studies, autoantibodies to survivin were detected in 27.1% of cancer dogs, and this represented a significant difference from control populations consisting of normal and non-cancer disease dogs [13]. The highest positivity rates (>50%) among cancer cases were seen in dogs with mammary tumor, squamous cell carcinoma and melanoma, suggesting that canine survivin is expressed in many canine melanoma tissues [13].…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…These diverse pathological changes in multiple organs are mainly due to focal or disseminated multiorgan vasculitis or perivasculitis of small blood vessels. The bacterium infects several types of nonphagocytic cells, such as endothelial cells and fibroblasts, as well as phagocytic macrophages, polymorphonuclear leukocytes (PMNs), and dendritic cells in vitro and in vivo (17)(18)(19)(20)(21). Previously, it was reported that increased autophagosomes were observed in PMNs after infection with O. tsutsugamushi (22).…”
mentioning
confidence: 99%